Timely diagnostics of hydraulic equipment in metallurgical production - E. V. Gapeenko (Литьë и металлургия, 2021)
Precision control of hydraulic equipment is a distinctive feature of modern hydraulic systems. With the help of special diagnostic devices, it is possible to reliably and simply monitor the operation of hydraulic equipment. Diagnostic methods can be very different. The article lists the stages and methods of checking hydraulic equipment malfunctions, as well as describes the principles of operation of diagnostic devices of well‑known world manufacturers HYDAC, MOOG, used in OJSC “BSW – Management Company of the Holding “BMC”. Schematically, the connection of the MOOG tester to the production equipment is presented when checking the servo valve in autonomous and combined mode, without resorting to dismantling the valve. Continuous monitoring of the oil purity with the help of the HYDAC FCU device allowed saving time on assessing its condition and taking fast‑acting corrective measures to clean the oil from contamination.